Analyzing Problem Solving Difficulties on Applied Military Operation Research - Bambang Suharjo (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
Operations Research is a scientific discipline that can be used to help make decisions in all fields. In the military field, the application of operations research is very much so that every officer must be able to apply it in carrying out his duties. Indonesian Navy officers received education about operations research, especially the analytic hierarchy process when they attended the Staff and Command College. A total of 20 student officers were examined to find out the difficulties they faced in solving problem solving for the analytic hierarchy process material through written answers to questions and in-depth interviews using Polya's problem-solving steps. The results obtained are that all officers did not experience problems at the time of problem identification. However, almost half of them experienced problems when planning solutions, carrying out calculations and conducting reviews. The recommendation submitted is to use a software application so that the calculations are correct and fast.